2011
DOI: 10.1016/j.stem.2011.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Demethylases Jhdm1a/1b Enhance Somatic Cell Reprogramming in a Vitamin-C-Dependent Manner

Abstract: Reprogramming of somatic cells into induced pluripotent stem cells (iPSCs) resets the epigenome to an embryonic-like state. Vitamin C enhances the reprogramming process, but the underlying mechanisms are unclear. Here we show that the histone demethylases Jhdm1a/1b are key effectors of somatic cell reprogramming downstream of vitamin C. We first observed that vitamin C induces H3K36me2/3 demethylation in mouse embryonic fibroblasts in culture and during reprogramming. We then identified Jhdm1a/1b, two known vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
370
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 418 publications
(388 citation statements)
references
References 51 publications
11
370
0
7
Order By: Relevance
“…These results indicate that AA can induce DNA demethylation mainly by enhancing the Tet-mediated oxidation of 5mC. The observation of the slight reduction in 5mC caused by AA in Tet1/Tet2-deleted cells ( Figure 5B) suggests one Tetunrelated but minor mechanism for AA-induced DNA demethylation, which is probably related to histone demethylases 28 AA Regulates a Potential Broad Functional Pathway by 5hmC Formation. To further explore the roles of AA on DNA modifications, we examined the genome-wide distribution and enrichment of 5hmC in mouse ES cells using a selective chemical labeling of 5hmC pull-down approach 33 coupled with deep-sequencing by Illumina HiSeq 2000 platform.…”
Section: ■ Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…These results indicate that AA can induce DNA demethylation mainly by enhancing the Tet-mediated oxidation of 5mC. The observation of the slight reduction in 5mC caused by AA in Tet1/Tet2-deleted cells ( Figure 5B) suggests one Tetunrelated but minor mechanism for AA-induced DNA demethylation, which is probably related to histone demethylases 28 AA Regulates a Potential Broad Functional Pathway by 5hmC Formation. To further explore the roles of AA on DNA modifications, we examined the genome-wide distribution and enrichment of 5hmC in mouse ES cells using a selective chemical labeling of 5hmC pull-down approach 33 coupled with deep-sequencing by Illumina HiSeq 2000 platform.…”
Section: ■ Introductionmentioning
confidence: 82%
“…25−29 Limited data suggested that this effect was probably associated with histone demethylases. 28 Since the histone-targeting demethylases cannot directly act on methylated DNA, we speculate that AA should be a better choice to be exploited by Tet dioxygenases to regulate DNA demethylation. The natural choice of nutrient AA would not sacrifice normal cellular functions in mammals.…”
Section: ■ Introductionmentioning
confidence: 97%
“…Consistently, it was found that vitamin C can enhance reprogramming in part by reducing p53 expression and alleviating senescence [71]. A recent study further showed that vitamin C promoted reprogramming also by modulating Jhdm1a/1b, two known vitamin Cdependent H3K36 histone demethylases that are potent regulators of reprogramming [72]. Consistently, Jhdm1b activation accelerates cell cycle progression and suppresses cellular senescence by repressing the INK4/ARF locus.…”
Section: Rationale-based Chemical Approachesmentioning
confidence: 73%
“…Among the molecules modulating specific signaling pathway or epigenetic state, ascorbic acid (Vitamin C, VC) is a star chemical, which enhanced reprogramming of mouse somatic cells (the human iPSCs culture medium contains VC) (Esteban et al, 2010). The mechanism of VC's function may link to its downstream factor Jhdm1a/1b, a histone demethylase responsible for H3K36me2 or H3K36me3 demethylation which in turn accelerates cell proliferation by repressing the Ink4/Arf locus (Wang et al, 2011). New mouse study from the Hochedlinger group showed that VC attenuated hypermethylation of Dlk1-Dio3 by disenabling intergenic differentially methylated region (IG-DMR) to recruit Dnmt3a (a DNA methyltransferase) in the progress of reprogramming.…”
mentioning
confidence: 99%